New Uniform Motion and Fermi-Walker Derivative of Normal Magnetic Biharmonic Particles in Heisenberg Space - Korpinar, Talat; Korpinar, Zeliha; Chu, Yu-Ming; Akinlar, Mehmet Ali; İnç, Mustafa (Mdpi, 2020)
In the present paper, we firstly discuss the normal biharmonic magnetic particles in the Heisenberg space. We express new uniform motions and its properties in the Heisenberg space. Moreover, we obtain a new uniform motion of Fermi-Walker derivative of normal magnetic biharmonic particles in the Heisenberg space. Finally, we investigate uniformly accelerated motion (UAM), the unchanged direction motion (UDM), and the uniformly circular motion (UCM) of the moving normal magnetic biharmonic particles in Heisenberg space.
Keywords: magnetic field; biharmonic particle; bienergy; Heisenberg space; Fermi-Walker derivative; symmetries